2023
DOI: 10.3390/nano13030484
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Antibacterial Activity in Tannic Acid–Iron Complexed Chitosan Films for Medical Device Applications

Abstract: Healthcare-associated infections (HAIs) represent a global burden, leading to significant mortality and generating financial costs. One important cause of HAIs is the microbiological contamination of implantable medical devices. In this context, a novel antimicrobial drug-eluting system, based on chitosan and loaded with gentamicin, a broad-spectrum antibiotic, was developed. The effects of the addition of tannic acid and different FeSO4 concentrations on the loaded antibiotic release were evaluated. The prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…Chitosan formulations used herein were based on a previous article from our group, in which tannic acid and iron (II) were used as crosslinkers to modulate the controlled release of gentamicin. The results indicated that release modulation occurs when the catechol/metal ion ratio was around 1:0.2 [33]. Consequently, the proportion of caffeic acid and copper presented herein follows this ratio.…”
Section: Chitosan Formulationsmentioning
confidence: 57%
“…Chitosan formulations used herein were based on a previous article from our group, in which tannic acid and iron (II) were used as crosslinkers to modulate the controlled release of gentamicin. The results indicated that release modulation occurs when the catechol/metal ion ratio was around 1:0.2 [33]. Consequently, the proportion of caffeic acid and copper presented herein follows this ratio.…”
Section: Chitosan Formulationsmentioning
confidence: 57%
“…Moreover, the aromatic esters in tannic acid were identified by characteristic bands at 1730–1705 cm –1 (CO stretching vibration) and 1100–1300 cm –1 (CO). The appearance of a peak at 1564 cm –1 , characteristic of the CC bond in the aromatic ring of poly-tannic acid, pointed to the presence of aromatic structures . Furthermore, the peak at 1210 cm –1 , corresponding to the COC bond, signified the presence of ether linkages within the poly-tannic acid structure.…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of a peak at 1564 cm −1 , characteristic of the C�C bond in the aromatic ring of poly-tannic acid, pointed to the presence of aromatic structures. 58 Furthermore, the peak at 1210 cm −1 , corresponding to the C�O�C bond, signified the presence of ether linkages within the poly-tannic acid structure. The peak at 754 cm −1 represented the distortion vibration of C�C in benzene rings, indicating the inclusion of hydrocarbon components in the poly-tannic acid's composition.…”
Section: Acs Sustainablementioning
confidence: 99%
“…24 Chevallier et al found that metal complexation with iron(III) improved chitosan membrane performance and metabolic activity of cells surfaced on the membrane. 25 TA/iron(III) complex deposition on the fiber is a popular research method, even though it is rare to use TA blended in the fiber to form a coating through complexation with Fe(III).…”
Section: Introductionmentioning
confidence: 99%
“…For the creation of multifunctional circulatory systems after implantation, TA-Fe­(III) coatings should be used in a variety of prevascularization applications along with other bioengineered materials with complicated porosity architectures. , Chinchilla et al prepared LDHs@TA–Fe­(III)/PCL nanocomposite films by one-step assembly of TA–Fe­(III) coatings . Chevallier et al found that metal complexation with iron­(III) improved chitosan membrane performance and metabolic activity of cells surfaced on the membrane . TA/iron­(III) complex deposition on the fiber is a popular research method, even though it is rare to use TA blended in the fiber to form a coating through complexation with Fe­(III).…”
Section: Introductionmentioning
confidence: 99%